(untitled) (Stamford Journal of Pharmaceutical Sciences, 2010)
Michelia champaca (Magnoliaceae) is a large medicinal plant which is traditionally used against a number of diseases including inflammatory conditions. In the present study crude methanol extract of M. champaca leaf was investigated for possible antioxidant, analgesic and cytotoxic activity. The extract showed remarkable antioxidant activity in DPPH radical scavenging activity, nitric oxide scavenging activity and total antioxidant capacity assays. In both DPPH radical and NO scavenging assay, the extract exhibited strong antioxidant activity and the IC50 values in DPPH radical scavenging and NO scavenging assays were found to be 30.07 μg/ml and 15.42 μg/ml, respectively while the IC50 values of ascorbic acid were 12.5 μg/ml and 4.07 μg/ml, respectively. Total antioxidant activity of the extract increased in a dose dependent manner. Analgesic activity of the crude extract was evaluated using acetic acid-induced writhing model of pain in mice. The crude extract at 200 mg/kg and 400 mg/kg b.w doses displayed significant (p < 0.001) reduction in acetic acid induced writhing in mice with a maximum effect of 68.7% reduction at 400 mg/kg b.w. which is comparable to the standard, diclofenac sodium (78.2%). The extract was also investigated for cytotoxic potential using Brine Shrimp lethality bioassay. In this bioassay the extract showed significant toxicity to Brine Shrimp nauplii with the LC50 value of 11.22 μg/ml. Results of the present study suggest that M. champaca leaf extract possesses strong antioxidant, analgesic and cytotoxic activity. Key words: Michelia champaca; Magnoliaceae; Antioxidant; Analgesic; Cytotoxicity. DOI: 10.3329/sjps.v2i2.5818 Stamford Journal of Pharmaceutical Sciences Vol.2(2) 2009: 1-7